Low Intestinal IL22 Associates With Increased Transplant-Related Mortality After Allogeneic Stem Cell Transplantation - Ghimire, Sakhila; Ederer, Katharina U.; Meedt, Elisabeth; Weber, Daniela; Matos, Carina; Hiergeist, Andreas; Zeman, Florian; Wolff, Daniel; Edinger, Matthias; Poeck, Hendrik; Herr, Wolfgang; Gessner, André; et al. (Frontiers in Immunology, 2022)
The role of IL-22 in adult patients undergoing allogeneic stem cell transplantation (SCT) is of major interest since animal studies showed a protective and regenerative effect of IL-22 in graft versus host disease (GvHD). However, no clinical data exist on the tissue expression. Here we demonstrate that patients not suffering from transplant-related mortality (TRM) show significantly upregulated IL22 expression during histological and clinical GI-GvHD (p = 0.048 and p = 0.022, respectively). In contrast, in GvHD patients suffering from TRM, IL22 was significantly lower (p = 0.007). Accordingly, lower IL22 was associated with a higher probability of TRM in survival analysis (p = 0.005). In a multivariable competing risk Cox regression analysis, low IL22 was identified as an independent risk factor for TRM (p = 0.007, hazard ratio 2.72, 95% CI 1.32 to 5.61). The expression of IL22 seemed to be microbiota dependent as broad-spectrum antibiotics significantly diminished IL22 expression (p = 0.019). Furthermore, IL22 expression significantly correlated with G-protein coupled receptor (GPR)43 (r = 0.263, p = 0.015) and GPR41 expression (r = 0.284, p = 0.009). In conclusion, our findings reveal an essential role of IL22 for the prognosis of patients undergoing allogeneic SCT.